2014
DOI: 10.1121/1.4893908
|View full text |Cite
|
Sign up to set email alerts
|

High frequency components of ship noise in shallow water with a discussion of implications for harbor porpoises (Phocoena phocoena)

Abstract: Growing ship traffic worldwide has led to increased vessel noise with possible negative impacts on marine life. Most research has focused on low frequency components of ship noise, but for high-frequency specialists, such as the harbor porpoise (Phocoena phocoena), medium-to-high frequency noise components are likely more of a concern. To test for biologically relevant levels of medium-to-high frequency vessel noise, different types of Automatic Identification System located vessels were recorded using a broad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
68
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(72 citation statements)
references
References 41 publications
3
68
1
Order By: Relevance
“…Both short-term (Thompson et al 2013a) and long-term displacement (Teilmann & Carstensen 2012) as well as changes in foraging behaviour (Pirotta et al 2014) have been reported as likely consequences of construction-related activity to this species. In addition, harbour porpoises are also likely to actively avoid vessels (Hermannsen et al 2014, Dyndo et al 2015; however, despite the present study finding evidence of constructionrelated activity reducing porpoise occurrence in the bay, it did not find any such pattern with respect to the number of vessels within the bay. Conversely, an increase in vessel numbers did have a strong, negative influence on the occurrence of common dolphins.…”
Section: Discussioncontrasting
confidence: 99%
“…Both short-term (Thompson et al 2013a) and long-term displacement (Teilmann & Carstensen 2012) as well as changes in foraging behaviour (Pirotta et al 2014) have been reported as likely consequences of construction-related activity to this species. In addition, harbour porpoises are also likely to actively avoid vessels (Hermannsen et al 2014, Dyndo et al 2015; however, despite the present study finding evidence of constructionrelated activity reducing porpoise occurrence in the bay, it did not find any such pattern with respect to the number of vessels within the bay. Conversely, an increase in vessel numbers did have a strong, negative influence on the occurrence of common dolphins.…”
Section: Discussioncontrasting
confidence: 99%
“…Although various studies have focused on the effect of whale and dolphin watching tourism on cetaceans [31, 37, 40, 42, 47–49], fewer studies have discussed local marine traffic and international maritime impact on harbour porpoises [50–53]. The current study revealed that Black Sea harbour porpoises spend half of their daylight time within the 400 m range of marine vessels throughout the Istanbul Strait, and that marine traffic induces significant changes not only on swimming direction but also on behavioural transitions.…”
Section: Discussionmentioning
confidence: 99%
“…3) were driven by identifiable sources of human activity (mainly shipping), rather than the contribution of natural noise sources. However, the current choice of MSFD frequency bands at 63 Hz and 125 Hz may inadequately reflect the risk of acoustic masking38, and can be contaminated by flow noise31, and higher frequency bands (e.g. at 250 or 500 Hz) appear to better correlate with broadband levels of shipping noise31.…”
Section: Discussionmentioning
confidence: 99%